Bioinspired Fabrication of Polyurethane/Regenerated Silk Fibroin Composite Fibres with Tubuliform Silk-Like Flat Stress–Strain Behaviour - Venkatesan, Harun (Polymers (Basel), 2018)
Tubuliform silk is one of the seven different types of spider silks, which is well known for its unique tensile behaviour with Flat Tensile Stress–Strain (FTSS) curve. It is found that anisotropic microstructure of β-sheets is responsible for this property. In recent years, bioinspired approaches to engineer fibres supported by modern manufacturing systems have been attracting considerable interest. The present paper aims to investigate a strategy to biomimic the FTSS behaviour of tubuliform silk in synthetic polymer composite fibres by blending polyurethane (PU) and regenerated silk fibroin (RSF) at different ratios. Wet spinning of composite fibres results in the reconstruction of β-sheets in the synthetic fibre matrix. PU/RSF composite fibre at a ratio of 75/25 produce a tensile curve with FTSS characteristics. Secondary structural changes in RSF and interchain directions of β-sheets within the fibre are studied using Fourier Transform Infra-red (FTIR) spectroscopy and Transmission Electron Microscopy (TEM), respectively. Interestingly, results of TEM patterns confirm transverse anisotropic properties of RSF β-sheets. The composite fibres also display tuneable mechanical properties with respect to RSF contents.